ANALISIS KETERKAITAN KEKERASAN DENGAN PERBUATAN CABUL TERHADAP ANAK - Yordan Triadi Wibowo; Ismawati Septiningsih (Verstek, 2023)
This article analyzes the relationship between violence and obscenity against children. This article aims to find out the relationship between violence and obscenity against children associated with doctrinal theories. This research was conducted using prescriptive doctrinal or normative legal research methods using primary and secondary legal sources which are of course related to the issues studied. The legal material collection technique used in this research is a literature study technique with a conceptual approach. Based on the results of the study, shows that violence against children using an object can be categorized as an obscenity against a child if it is aimed at a child's genitals.Keywords: Child;Violence; Obscenity